1999
DOI: 10.4269/ajtmh.1999.60.421
|View full text |Cite
|
Sign up to set email alerts
|

Malaria vectors in a traditional dry zone village in Sri Lanka.

Abstract: Abstract. Malaria transmission by anopheline mosquitoes was studied in a traditional tank-irrigation-based riceproducing village in the malaria-endemic low country dry zone of northcentral Sri Lanka during the period August 1994-February 1997. Adult mosquitoes were collected from human and bovid bait catches, bovid-baited trap huts, indoor catches, and pit traps. Mosquito head-thoraces were tested for the presence of Plasmodium falciparum and P. vivax, and blood-engorged abdomens for the presence of human bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 20 publications
3
64
1
Order By: Relevance
“…For example, in Sri Lanka the main vector driving malaria transmission is Anopheles culicifacies (Amerasinghe et al, 1999) which readily breeds in streambed pools that are not directly rainfall-fed (Amerasinghe et al, 1997;van der Hoek et al, 1998a). Despite the presence of multiple alternative sources of surface water, van der Hoek et al (2003) found that malaria risk was elevated within a zone up to 750 m from the river.…”
Section: River Channels and Floodplains As Breeding Habitatsmentioning
confidence: 99%
“…For example, in Sri Lanka the main vector driving malaria transmission is Anopheles culicifacies (Amerasinghe et al, 1999) which readily breeds in streambed pools that are not directly rainfall-fed (Amerasinghe et al, 1997;van der Hoek et al, 1998a). Despite the presence of multiple alternative sources of surface water, van der Hoek et al (2003) found that malaria risk was elevated within a zone up to 750 m from the river.…”
Section: River Channels and Floodplains As Breeding Habitatsmentioning
confidence: 99%
“…Paddy fields, irrigation systems and peridomestic environments facilitate breeding of vectors of malaria, lymphatic filariasis, Japanese encephalitis and dengue. [11][12][13][14][15] Additionally, the use of insecticides may cause acute poisoning and leave toxic residues in food; 16,17 resistance may develop in vector populations against the insecticides used for control; 18,19 and biodiversity may be degraded, which may contribute to a resurgence of mosquitoes. 20,21 Therefore, convergence is needed between integrated pest management strategies and integrated vector management strategies to help farmers improve their agricultural practices while minimizing environmental risks to health.…”
Section: The Problemsmentioning
confidence: 99%
“…varuna has been found infected with P. falciparum and P. vivax by circum- sporozoite ELISA, and it was implicated in a relatively low level of malaria transmission in a traditional tank-irrigationbased rice-producing village. 12,13 The population in Binh Thuan Province of Vietnam, however, is highly zoophilic, and on the basis of this behavior, it cannot be considered as a malaria vector in that area of the country. Moreover, the circumsporozoite ELISA assay on An.…”
Section: Resultsmentioning
confidence: 99%